SISTEM INFORMASI KLINIK FACHRI OEMRAN - , MUTIARA SANTIKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
General clinic as one that provides health care services. One of the health care units are often targeted people of Cirebon to take medication that Fachri Oemran Clinic. In terms of data processing, Clinical Fachri Oemran still do it manually. Which cause many problems, such as filling the data is still in the paper, so that the rate of loss and damage to the data is quite large. Therefore we need an information system that can assist in the processing of the output data and is able to present, either in the form of information and reports as appropriate. The information system in this clinic was built by using Apache webserver, data base MySQL, and programming framework CodeIgniter language. This information system handle data processing which in the form of patient data, result of inspection data or medical record, medicine data, medical action, diagnosa and detail diagnosa data, payment data, medicine warehouse data and report making in the form of table. After being examined successfully, this information system is proven able to ease in registration process, examination process, transaction or payment process, processing data such as